2015
DOI: 10.1001/jamaoncol.2015.23
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diagnosis and Clinical Follow-up of Monoclonal Gammopathy of Undetermined Significance on Survival in Multiple Myeloma

Abstract: Patients with MM with prior knowledge of MGUS had better MM survival, suggesting that earlier treatment of MM leads to better survival. The observation that a low M-protein concentration at MGUS diagnosis was associated with poorer MM survival may reflect less frequent clinical follow-up. Our observations stress the importance of clinical follow-up in patients with MGUS, regardless of risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 23 publications
3
116
0
2
Order By: Relevance
“…At the moment of diagnosis, the following baseline prognostic factors were recorded: age, sex, Eastern Cooperative Oncology Group performance status score, the occurrence of weight loss, body mass index, number of comorbidities, diagnostic delay, treatment delay, presence of previously documented precursor disease [27], International Staging System (ISS), light chain MM [28], percentage of bone marrow plasma cells by morphology, serum creatinine (mg/dL), estimated glomerular filtration rate (mL/min/1.73 m 2 ), free light chain ratio (involved/uninvolved), lactate dehydrogenase (U/L), high-risk [t (4;14), t(14;16), 11q, and del(17p)] cytogenetic abnormalities by fluorescent in situ hybridization, and extramedullary disease by positron emission tomography with 18 fluorine-fluoro-deoxyglucose integrated with computed tomography.…”
Section: Methodsmentioning
confidence: 99%
“…At the moment of diagnosis, the following baseline prognostic factors were recorded: age, sex, Eastern Cooperative Oncology Group performance status score, the occurrence of weight loss, body mass index, number of comorbidities, diagnostic delay, treatment delay, presence of previously documented precursor disease [27], International Staging System (ISS), light chain MM [28], percentage of bone marrow plasma cells by morphology, serum creatinine (mg/dL), estimated glomerular filtration rate (mL/min/1.73 m 2 ), free light chain ratio (involved/uninvolved), lactate dehydrogenase (U/L), high-risk [t (4;14), t(14;16), 11q, and del(17p)] cytogenetic abnormalities by fluorescent in situ hybridization, and extramedullary disease by positron emission tomography with 18 fluorine-fluoro-deoxyglucose integrated with computed tomography.…”
Section: Methodsmentioning
confidence: 99%
“…The challenges of diagnosing multiple myeloma include the need for clinicopathological symptoms; summarized by the acronym CRAB: increased serum Calcium concentration, Renal insufficiency, Anemia, and lytic Bone lesions. In multiple myeloma, early detection is associated with 15% better overall survival [19] and less severe complications [20]. In order to intervene in high-risk SMM prior to end organ damage, the International Myeloma Working Group (IMWG) has recently updated the definition of multiple myeloma by adding three biomarker-characterized myeloma defining events to the CRAB acronym: 1) presence of bone marrow plasma cells > 60% as a differentiation from smoldering multiple myeloma; 2) serum of involved FLC ratio is > 100; 3) magnetic resonance imaging (MRI) with more than one skeletal focal lesion ( Table 2).…”
Section: Monoclonal Gammopathies Overview and Categorizationmentioning
confidence: 99%
“…This may avoid hospitalizations and costs and also preserve quality of life. Indeed, two recent population studies have shown benefits of MGUS follow-up [68,69]. First, a Swedish study showed improved survival of MM patients with prior knowledge of MGUS, suggesting that earlier treatment of MM leads to better survival [69].…”
Section: Fo Ll Ow-u P Follow-up Of Mgus Patientsmentioning
confidence: 99%
“…Indeed, two recent population studies have shown benefits of MGUS follow-up [68,69]. First, a Swedish study showed improved survival of MM patients with prior knowledge of MGUS, suggesting that earlier treatment of MM leads to better survival [69]. Secondly, the SEER database analysis showed that MGUS follow-up was an independent predictor of lower rates of complications at the diagnosis of malignancy [68].…”
Section: Fo Ll Ow-u P Follow-up Of Mgus Patientsmentioning
confidence: 99%